Dynamic monitoring of viral gene expression reveals rapid antiviral effects of CD8 T cells recognizing the HCMV-pp65 antigen - Khan, Fawad; Müller, Thomas R.; Kasmapour, Bahram; Ynga-Durand, Mario Alberto; Eiz-Vesper, Britta; von Einem, Jens; Busch, Dirk H.; Cicin-Sain, Luka (Frontiers in Immunology, 2024)
Human Cytomegalovirus (HCMV) is a betaherpesvirus that causes severe disease in immunocompromised transplant recipients. Immunotherapy with CD8 T cells specific for HCMV antigens presented on HLA class-I molecules is explored as strategy for long-term relief to such patients, but the antiviral effectiveness of T cell preparations cannot be efficiently predicted by available methods. Therefore, we developed an Assay for Rapid Measurement of Antiviral T-cell Activity (ARMATA) by real-time automated fluorescent microscopy and used it to study the ability of CD8 T cells to neutralize HCMV and control its spread. As a proof of principle, we used TCR-transgenic T cells specific for the immunodominant HLA-A02restricted tegumental phosphoprotein pp65. pp65 expression follows an early/late kinetic, but it is not clear at which stage of the virus cycle it acts as an antigen. We measured control of HCMV infection by T cells as early as 6 hours post infection (hpi). The timing of the antigen recognition indicated that it occurred before the late phase of the virus cycle, but also that virion-associated pp65 was not recognized during virus entry into cells. Monitoring of pp65 gene expression dynamics by reporter fluorescent genes revealed that pp65 was detectable as early as 6 hpi, and that a second and much larger bout of expression occurs in the late phase of the virus cycle by 48 hpi. Since transgenic (Tg)-pp65 specific CD8 T cells were activated even when DNA replication was blocked, our data argue that pp65 acts as an early virus gene for immunological purposes. Therefore, ARMATA does not only allow same-day identification of antiviral T-cell activity, but also provides a method to define the timing of antigen recognition in the context of HCMV infection.